Sworn Sign Language Interpreters Provision for Deaf People Appearing before Notary Based on Justice Principle - Kurniawan, Elvaretha Natalia; Dewi, Amelia Sri Kusuma; Susilo, Hariyanto (International Journal of Business, Law, and Education, 2024)
This study is motivated by the incompleteness of law in Law Number 2 of 2014 concerning Amendments to Law Number 30 of 2004 concerning the Position of Notaries. The aims of this study are to (1) Identify the laws and regulations in Indonesia regarding the fulfillment of the rights of deaf people who appear before a notary who fulfill the principles of justice and (2) Analyze the regulatory concept regarding the provision of sworn sign language interpreters for deaf people who appear before a notary who fulfill the principles of justice. This study used normative juridical methods through a statutory approach and a conceptual approach. Moreover, legal materials were analyzed through grammatical and systematic interpretation analysis methods. The results of this study show that the Law on Notary Positions and its Amendments does not regulate the provision of sworn sign language interpreters for deaf people who appear before a notary to conduct legal actions in an authentic deed. In addition, it does not regulate the mechanism for a notary’s obligation to read an authentic deed in front of interested parties so that a sworn sign language interpreter is required in the process of signing the deed in order to verifying the deed in order to create balanced justice in Law on Notary Position and its Amendments.